Reaching Out to an Audience: Using Movie Maker in Nurses' English class - Zuraina, Ali; Azwin Arif, Abdul Rahim; Nor Yazi, Khamis; Suriya Kumar, Sinnadurai (2009)
Educating and creating public awareness about health should stimulate and impact. This paper shall discuss the use of a task-based approach by exploiting technology, explicitly the use of Movie Maker in an ESL classroom among nurses at college, as a valuable alternative in reaching out to the public. As a part of their English language assessment, 70 first year student nurses from Kuantan Nursing College (Malaysia) enrolled in a one-day workshop in producing their own movie. In groups of three to four, the students were given the autonomy to choose topics related to a disease, and to be prepared beforehand. At the end of the 2-hour preparation, members of each group got the chance to explain the disease with the help of the movie of their creation. Through questionnaires and interviews, the sample found the effort significant to them as it has helped them to make the explanation not only more interesting but more vivid with the help of moving pictures, relevant sounds and bold or highlighted important words. Despite their acceptance of the technology the sample found that they need to be more careful with their choice of words, especially in treatments, in order to make more impact on their audience.